Basis of Efficient Cash Flow Management of the Enterprise - Eshonqulov Akmal Qudratovich (Research Parks Publishers, 2022)
The urgency of the problem of managing the cash flows of organizations is of particular importance today. Cash flow management is a necessary tool for making a profit for any organization.